Experimental and numerical studies of fire behavior of cold-formed steel center-sheathed walls subjected to gravity loading - Xing, Yonghui (2023)
It is a challenge for the conventional cold-formed steel (CFS) sheathed wall system to be adopted in multi-story buildings due to its limited lateral load capacity and stiffness. Therefore, an innovative cold-formed steel center-sheathed shear wall (CFSCSSW) system with better lateral load capacity and stiffness has been proposed and shown its potential application in multi-story buildings. However, the fire performance of CFSCSSW has become one of the major issues which have yet to be investigated and thus become the focus of the present paper, underpinned by tests and numerical simulations. In this study, a full-scale test at room temperature was firstly conducted on a CFSCSSW to obtain its vertical load capacity, while another four full-scale fire tests were then carried out with applied gravity loads to investigate the influence of the interior stud, load ratio, and aspect ratio on fire behavior of the walls. Following the tests, 11 finite element models were subsequently developed to investigate the influence of various critical parameters, such as the axial load ratio, aspect ratio, and end stud thickness, on the fire resistance of CFSCSSW. The fire test results showed that the heat loss of the wall surface could be more than 40% during the temperature transition from the fire exposed side to the cold side. It is found that the presence of interior stud, increasing the aspect ratio beyond 3.0 as well as the load ratio to be greater than 0.3 can result in a transition of the failure mode of the wall from global buckling to local buckling. The critical temperature declines approximately 12% if the load ratio increases by 0.1. The fire resistance of the wall was slightly improved with the increase of the aspect ratio. The end stud thickness of 2 mm is recommended preferentially based on the parametric results. In addition, it was found that the presence of the interior stud has little influence on the fire resistance of the walls.